Measuring the impact of an empiric antibiotic algorithm for pulmonary exacerbation in children and young adults with cystic fibrosis. Issue 4 (4th February 2022) - Kennedy, Charles; Greenberg, Isabella; Perez, Geovanny F.; Chaney, Hollis; Sami, Iman; Ogunlesi, Folasade; Koumbourlis, Anastassios C.; Hammer, Benjamin; Hamdy, Rana F.; Cogen, Jonathan D.; Payne, Asha S.; Hahn, Andrea
Abstract: Background: Antimicrobial stewardship is a systematic effort to change prescribing attitudes that can provide benefit in the provision of care to persons with cystic fibrosis (CF). Our objective was to decrease the unwarranted use of broad‐spectrum antibiotics and assess the impact of an empiric antibiotic algorithm using quality improvement methodology. Methods: We assembled a multidisciplinary team with expertise in CF. We assessed baseline antibiotic use for treatment of pulmonary exacerbation (PEx) and developed an algorithm to guide empiric antibiotic therapy. We included persons with CF admitted to Children's National Hospital for treatment of PEx between January 2017 and March 2020. Our primary outcome measure was reducing unnecessary broad‐spectrum antibiotic use, measured by use consistent with the empiric antibiotic algorithm. The primary intervention was the initiation of the algorithm. Secondary outcomes included documentation of justification for broad‐spectrum antibiotic use and use of infectious disease (ID) consult. Results: Data were collected from 56 persons with CF who had a total of 226 PEx events. The mean age at first PEx was 12 (SD 6.7) years; 55% were female, 80% were white, and 29% were Hispanic. After initiation of the algorithm, the proportion of PEx with antibiotic use consistent with the algorithm increased from 46.2% to 79.5%. Documentation of justification for broad‐spectrum antibiotics increased from 56% to 85%. Use of ID consults increased from 17% to 54%. Conclusion: Antimicrobial stewardship initiatives are beneficial in standardizing care and fostering positive working relationships between CF pulmonologists, ID physicians, and pharmacists.